Treatment Outcomes for Asian Americans Diagnosed with Schizophrenia Spectrum Disorder. - Lim, Caroline; Um, Mee Young; Schott, Erik; Arkadie, Nicole; Hernandez, Mercedes; Barrio, Concepción (Community Mental Health Journal, 2025)
We implemented a pilot study to investigate symptoms and functional outcomes of Asian Americans treated in urban community mental health centers for a diagnosis of schizophrenia spectrum disorder. Furthermore, we investigated whether these outcomes differed between East and Southeast Asians. We collected quantitative data from 75 participants recruited using a nonprobability sampling strategy from six urban community mental health centers. We used the Positive and Negative Syndrome Scale (Kay et al. in Schizophrenia Bulletin 13(2):261–276, 1987) and the Strauss and Carpenter Outcome Scale (Strauss and Carpenter in Archives of General Psychiatry 27(6):739–746, 1972) to measure their symptoms and functional outcomes. To compare the outcomes between East and Southeast Asians, we used a multivariable logistic regression model, which adjusted for the estimated effects of age, sex assigned at birth, and age at onset of illness for each outcome examined. The data shows that the treatment outcomes for this group are poor. Only a small number of participants experienced symptomatic remission (30.67%), role restoration (34.67%), and clinical recovery (21.33%). The majority of those who did not experience clinical recovery had difficulties sustaining symptomatic remission and restoring role functioning (54.67%). However, more participants achieved social restoration (68.00%). The results did not vary by national origin groups and sex assigned at birth. However, the participant's age, the age at which the illness began, or both determined whether the treatment outcomes were favorable. Findings underscore the need for interventions that improve symptom control to increase the likelihood of other favorable outcomes.